INVESTIGASI PERILAKU OVIPOSISI Aedes aegypti PADA PERBEDAAN WARNA WADAH PENAMPUNGAN AIR DI KOTA MATARAM - Munawir Sazali; Syafrina Sari Lubis (Jurnal Inovasi Pendidikan dan Sains, 2024)
Dengue fever was an endemic disease that transmission from Aedes sp. bites. The spread epidemic disease of dengue fever in an area was caused highest vector dengue virus population, it’s bolstered by water container as canister oviposition of Aedes aegypti at difference position (indoor and outdoor). Water container has been finding at residence area such as bathtub, well, disposal plastic, crockery, etc. This study aims to investigation oviposition process Ae. aegypti populations at Pagutan Sub-district in Mataram City. The research was explanatory in prevention community trial research. Based on data egg collection was known oviposition behavior of the mosquito, it was attracted to dark color water container at the indoor and outdoor position. The difference of color water container and position were the significant difference (p=0.000<0.05), it was found significant difference dark color of water container at an indoor position with bright and white color water container at an indoor position, and significant difference with dark, bright and white color at an outdoor position. Oviposition behavior of dengue vector viruses was developed as biological control of Aedes sp. based on color of water container.